Asia : a concise history - Cotterell, Arthur (Singapore : John Wiley & Sons (Asia), 2011)
'A comprehensive narrative of the 3,000 years that have formed Asia's people, culture, and global destiny. Tracing its origins in esopotamia to its modern role on the global geopolitical stage, historian Arthur Cotterell offers a compelling, lively, and readable account of one of the most culturally diverse, and often misunderstood, parts of the world. Beginning with the emergence of the world's earliest civilization in 3000 BC, Asia: A Concise History provides a fascinating look at the global convulsions like the rise and fall of Assyria and Persia, the medieval states that flourished after the advent of Islam, and the modern transformations triggered by the lightning conquests of imperial Japan that have shaped the continent. Covers the great events and figures of Asian history, along with a look at the monumental remains that bear witness to those times: the ziggurats of Iraq, the Taj Mahal, the Great Wall of China, the temple of Angkor Wat. Includes scinating slices of history, including funeral arrangements for Qin Shi Huangdi in 210 BC, an extract from Lord Macartney's journal of his 1793 diplomatic mission to the Qing emperor Qian Long, and Toyotomi Hideyoshi's edict of 1587 banning firearms in Japan. Features boxed inserts of special interest like a Babylonian recipe for lamb stew circa 1500 BC. Contains over 100 illustrations, maps, and photos'--Publisher's description.
Includes bibliographical references (p. 444-452) and index.
Keywords: Asia -- History